Chemical kinetic numerical of analysis of NOx removal by negative corona discharge - Souhaila ASKRI; Abdel Karim FEROUANI; Mostefa LEMERINI; Elhabib GUEDDA (Universty of El-oued جامعة الوادي, 2019)
This study presents a chemical kinetic analysis of different species involved in nitrogen-oxygen mixed gas treated by stationary negative corona discharge at atmospheric pressure. We take account 16 different chemical species reacting following 120 selected chemicals reactions. The mathematical model used consists of a system of equations that takes into account the variation of the density and the chemical kinetics of the environment. The reaction rate coefficients are taken from the literature. We analyse especially, the temporal evolution (10-9 – 10-3 s) of NO, NO2 , NO3 and N2O5 species under different values of electrical field. The results show that the evolution of these nitrous oxides is substantially affected by the application of the electrical discharge. This allows us the important role played by the negative corona discharge in NOx removing.
Intervention
Keywords: Nitrogen oxide; NOx reduction; rate reaction; reduced electric field